Replays of Reports, Songs
Report with guest speaking about the bright victory that is coming; civil defence forces in Najaf destroying leftovers from bombs; political speech from Saddam to his nation and army; report on how life is running as normal; report on bombing of civilian area, school, kindergarten, Mosque, living complex; report on bombing in Basra, where church and civilian areas were targets; report on downing of American plane; report on bombing near Russian Embassy; report on pictures from "final battle"; songs are interspersed.